Motivation in Nursing Education: Intrinsic and Extrinsic Motivation Resources of Students - Ayşe Çiçek Korkmaz; Nuriye Nesrin İpekçi (Association of Nurse Managers, 2016)
INTRODUCTION: The aim of this study is to examine the motivation resources and problems of nursing students in terms of different variables. METHODS: This descriptive research was realized with 118 students who were the 3rd and 4th graders of the Nursing Department of a Health College of a University within the month of March during the Academic Year of 2013-2014. The data was collected by using the questionnaire form, 'Motivation Resources and Problems Scale.' Descriptive statistics methods (frequency and percentiles), t test and One-Way ANOVA test in independent groups were used for data analysis. RESULTS: Mean interior, and exterior motivation subscale scores were 40.98+-7.93 pts, and 21.18+-3.31pts, respectively. A statistically significant difference between the mean scores of the students' interior motivation subscale items (grade, department satisfaction and the reasons of preferring the profession) and also, between the mean scores of exterior motivation subscale items (department satisfaction and reasons of preferring the profession) was determined (p<0.05). DISCUSSION AND CONCLUSION: It was found out that the interior and exterior motivation levels of the nursing students were high, the negative motivation was low. The factors which demotivate students must be determined and precautions must be taken.